Can Neo-Rural Initiatives Bolster Community Resilience in Depopulated Coupled Human and Natural System?: Insights From Stakeholder Perceptions in Central Spain - Sansilvestri, Roxane; de Lucio, José Vicente; Seijo, Francisco; Zavala, Miguel A. (Frontiers in Environmental Science, 2022)
Preindustrial era agro-sylvopastoral land uses have influenced structure, function and disturbance in Mediterranean type mountainous landscapes for millennia. In this study we analyze through semi-structured interviews, stakeholder perceptions of coupled human and natural system (CHANS) community resilience in one such landscape; the municipality of Puebla de la Sierra, Madrid. The municipality is part of the Biosphere Reserve of the Sierra del Rincon and the Natura 2000 network and as such is subject to various conservationist measures and regulations emanating from multiple levels of governance. In the preindustrial past most municipal lands formed an oak “dehesa” or hollowed out forest CHANS that made biomass extraction through pollarding compatible with pastoralism and shifting agriculture. After a period of rapid transformation in the early 20th century - marked by the state led plantation of coniferous forests, the final third of the last century was characterized by rural abandonment and the collapse of traditional forms of land use as well as the gradual transformation of the municipality into an eco-touristic, exurban destination for Madrid residents. More recently, initiatives have emerged from neo-rural settlers in the area wishing to connect traditional knowledge and management with modern agro-environmental practices. As a result of our study, we identified two limiting factors to community resilience in this CHANS; governance and financing. The current governance model was perceived by respondents as contrary to their reality and needs, which translates into environmental, urban and health regulations that penalize agroecological and small-scale production economic uses of the ecosystem. In addition, there is a lack of material and financial resources to initiate these transformative local actions which further weakens community resilience. Stakeholders however also identified other factors that reinforce community resilience such as a communal willingness to revive key traditional ecosystem management practices such as pollarding, the trust existing between the people participating in these new initiatives and the capacity for deliberating between different visions of future development pathways amongst local stakeholders.